Operative Method for Transverse Colon Carcinoma: Transverse Colectomy Versus Extended Colectomy. Issue 7 (July 2016) - Chong, Choon Seng; Huh, Jung Wook; Oh, Bo Young; Park, Yoon Ah; Cho, Yong Beom; Yun, Seong Hyeon; Kim, Hee Cheol; Lee, Woo Yong
Abstract : BACKGROUND: The type of surgery performed for primary transverse colon cancer varies based on tumor characteristics and surgeon perspective. The optimal oncological outcome following different surgical options has not been clearly established, and transverse colectomy has shown oncological equivalence only in small cohort studies. OBJECTIVE: Our aim was to compare long-term oncological outcomes after transverse colectomy versus extended resection for transverse colon cancer. DESIGN: This study is a retrospective review of prospectively collected data. SETTING: This study was conducted at a tertiary care hospital. METHOD: All patients treated for transverse colon cancer at the Samsung Medical Center between 1995 and 2013 were included. MAIN OUTCOME MEASURES: Oncological outcomes were compared between 2 groups of patients: a transverse colectomy group and an extended colectomy group (which included extended right hemicolectomy and left hemicolectomy). RESULTS: A total of 1066 patients were included, of whom 750 (70.4%) underwent extended right hemicolectomy, 127 (11.9%) underwent transverse colectomy, and 189 (17.7%) underwent left hemicolectomy. According to univariate analysis, surgical approach, histological type, tumor morphology, cancer T and N stage, cancer size, and lymphovascular invasion were significant factors contributing to disease-free survival (DFS). However, as seen in multivariate analysis, only node-positive disease (HR = 2.035 (1.188–3.484)), tumors with ulcerative morphology (HR = 3.643 (1.132–11.725)), and the presence of vascular invasion (HR = 2.569 (1.455–4.538)) were significant factors for DFS. Further analysis with a propensity-matched cohort between the transverse and extended colectomy groups demonstrated no significant differences in DFS and overall survival. LIMITATIONS: This study was limited because it was performed at a single institution and it was retrospective in nature. CONCLUSION: In terms of perioperative and oncological outcomes, transverse colectomy and extended colectomy did not differ despite a shorter specimen length and fewer lymph nodes harvested in the transverse colectomy group. Independent prognostic factors for DFS were node-positive disease, the presence of vascular invasion, and ulcerative morphology.